Biology of limnocharis flava (L.) buchenau and neptunia oleracea lour. and their status as vegetable crops in Sarawak, Malaysia - Saupi, Noorasmah (2014)
The invasion and fast growth of aquatic macrophytes, Limnocharis flava (L.) Buchenau and Neptunia oleracea Lour. caused problems in rice fields and drainage systems. However, they are also offered for sale in native markets and being consumed as leafy vegetables among local urban peoples mainly in central region of Sarawak, Malaysia. These aquatic weeds are harvested from the wild, and there has been no attempt to cultivate them. Hence, this research evaluates their distribution and determine their ecological and morphological characteristics, i.e., habitats and plant adaptations to environments. These information were used for observational and detailed studies on developmental stages, crop and yield patterns, and the availability of these vegetables in native markets and further evaluates their nutritive status. Limnocharis flava were recorded growing in various habitats of 32 locations, i.e., township and residential ditches, oil palm plantation irrigation and roadside drainage systems. Based on Principal Component Analysis (PCA) of the various environmental parameters, three distinct environments formed the growing sites of L. flava, i.e., group A – areas with pH 5.01 – 5.50 and high water temperature, 33.01 – 34.00°C, group B – areas with low water temperature, 27.01 – 28.00°C that flow from roadside drainage system and group C – areas with slow moving water in wide drainage system, 2.0 – 2.5 m with water depth of 1.0 – 1.5 m. Plants grew densely in ditch which had comparatively high concentration of dissolved PO4 3-, NH3 - and NO2 - and total N and C, available P, K, Na, Mg and Mn in substrate, e.g., at Public Library Mukah and possessed relatively longer petiole and sheath length, and also bigger blade, floral structures, fruit and seed. There are three types of plant life forms, i.e., submerged, emergent and semi aquatic or marginally. The submerged life form was observed from seed germination to the juvenile plant stage and rarely occurred in the adult mature plant. The submerged juvenile plants’ leaves lacked stomata on both surfaces. The plant propagated through seed and plantlet. The plant developed from seed to reproductive plant within 20 to 28 days that involved seven developmental stages, i.e., swollen seed, germinating seed, seedling, juvenile plant with plumular leaves, juvenile plant with petiolate leaves, mature vegetative and reproductive plants. New plantlet emerges in the middle of the umbel inflorescence of the reproductive plant which then grew into new vegetative and reproductive plants. For N. oleracea, the plants showed two life forms as adaption to the environments, i.e., terrestrial (at Kg Medong and Kg Kekan) and floating (at Kg Penipah). However, the terrestrial life form is less common. The terrestrial plant had woodier stem than the floating plant. The stems were enveloped by thick white aerhenchyma tissues formed when stem is in contact with water within 6 to 8 days. It grew densely in the ditch which had comparatively high concentration of dissolved NO2 -, NO3 - and NH3 - and total N and available Na in substrate, e.g., at Kg Penipah. The plant propagated through seed and stem cutting. Six developmental stages were observed during development from seed to reproductive plant which took 24 to 26 days, i.e., swollen seed, germinating seed, seedling, juvenile plant, mature vegetative and reproductive plants. Auxiliary buds were also observed at the stem of N. oleracea which then developed into new vegetative and reproductive plants. Limnocharis flava and N. oleracea can be propagated in created environment, e.g., in tank. NO3 - or a combination of nutrient (NO2 -, NO3 - and NH3 -) responsible in the increased in number of leaf and inflorescence, blade length and width, and petiole diameter of L. flava propagated from seed and plantlet. As for propagation of N. oleracea, only NO3 - was responsible in the increased in length of plant grown from seed and stem cutting. Seven harvesting activities at two weeks interval performed after five weeks of transplanting showed there were no differences in the yield of L. flava shoots. For N. oleracea propagation from seed and stem cutting, allowed eight harvesting activities at one week interval after five weeks transplanting also showed there were no differences in the yield of shoots. In the evaluation of plant availability in native markets, L. flava were available in the months of January to April, June to July and October in Sibu central market and in February to March in Bintulu tamu. As for N. oleracea, it was available only in April and October in Sibu central market. The periodic availability of these plants in native markets was attributed to the preference of other high profitable commodities, e.g., Durio zibethinus and endemic fruit, Canarium odontophyllum. Tender shoots comprising leaves and inflorescences were consumed raw or blanched or stir-fried. The proximate composition and mineral content analysis revealed that, both L. flava and N. oleracea possessed high moisture content of 83.75 – 94.59%. Limnocharis flava was also high in crude fat content (0.12 – 0.39%), while N. oleracea was identified as having high in protein content (3.01 – 3.23%). The tank culture is the favorable method for continuously production instead of gathering the plants from the wild. However, it is necessary to evaluate the annual production of these species at bigger-scale experiments. Other analyses on vitamins, anti-oxidants, antinutritional and toxicological are important to evaluate other usefulness of the plant properties.